Dominica. Significant achievements 2013 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Dominica during 2013 are identified, with respect to the needs and interests of the country, strengthening issues such as agribusiness, trade, export, leadership, food safety and workshops. Finally, support was given to improving quality standards, agri-food chains, the inclusion of women and the value chains of onion and sorrel.